Awareness and Perception Toward Heritage, Life, and Tourism in Converting Tourism Area - HYASAT, Ali S. (Journal of Environmental Management and Tourism; Vol 14 No 8 (2023): JEMT, Volume XIV, Issue 8(72), Winter 2023DO - 10.14505/jemt.v14.8(72).03, 2023)
The transformation of local areas to a tourism destination requires high awareness and perception of local community about the tourism activities and the consequences evolved of this involvement including the economic changes. This study examines the level of awareness of local communities regarding their role in the development of tourism in their city, particularly in rural areas since the transformation to a tourism destination was made by the governmental arrangements. A quantitative research approach was used. The population formed the local community of the city. A simple random sample composed of 700 citizens was selected to represent different community categories. The validity and reliability of the questionnaire was measured through a pilot sample. The results show the high validity and reliability of the data collection tool. The findings indicate that citizens were satisfied with the tourism development but expressed concern about its impact on their culture and privacy. The level of participation was found to be insufficient due to a lack of awareness of their role in the process. Negative perceptions regarding the quality of life also hindered their participation in local area development. The study recommends the official organization of the city's conversion to a tourism destination, including improvements in infrastructure and greater participation from locals.